Oblique Intraplate Convergence of the Seram Trough, Indonesia - Adi Patria; Robert Hall (Marine Geological Institute of Indonesia, 2018)
The Banda Arc which curves around through 180o is one of interesting features in Eastern Indonesia, a complex area resulting from convergence of Indo–Australia, Eurasia, and Pacific plates with a number of microplates involved. Its complexity has led to debates on how the U–shaped geometry was attained. This study investigates seafloor morphology and seismicity around the Seram Trough which may help to give an insight into the tectonic setting of the area. We further discuss each model proposed for the Seram Trough by previous authors. Generally, there are two views on how many slabs are subducting beneath the Banda Arc, either double slabs or single slab. The Seram Trough, which is often linked to the Timor–Tanimbar Trough enclosing the Banda Arc, was interpreted in different ways, with many models by many authors, as a subduction trench, an intraplate foredeep and a zone of strike–slip faulting. We argue that the most plausible explanation is a single slab model to explain the nature of the Banda Arc. The most plausible model for the Seram Trough is a foredeep model which is associated with exhumation processes on Seram and the deep feature was caused by a subsidence, led by loading by the fold–thrust belt. The Seram Trough is significantly different to common subduction systems. It has shallower bathymetry, is less than 3000 m in depth and is an almost aseismic zone. Keywords: Banda Arc, Buru Basin, convergence, fold–thrust belt, Seram Trough.Busur Banda yang melengkung 180o merupakan fitur menarik di Indonesia bagian timur, suatu area kompleks hasil konvergensi lempeng Indo–Australia, Eurasia dan Pasifik dengan beberapa lempeng mikro terlibat. Kompleksitasnya mengarah pada perdebatan bagaimana geometri ‘U’ terbentuk. Studi ini menginvestigasi morfologi dasar laut dan kegempaan disekitar Palung Seram yang dapat membantu memberikan wawasan tentang tatanan tektonik area tersebut. Kami juga mendiskusikan setiap model yang diajukan untuk Palung Seram oleh beberapa penulis sebelumnya. Umumnya, terdapat dua penjelasan tentang berapa jumlah lempeng yang menunjam dibawah Busur Sunda, antara dua lempeng atau satu lempeng. Palung Seram yang sering dihubungkan dengan Palung Timor-Tanimbar menyelubungi Busur Banda telah diinterpretasikan dengan beberapa model oleh beberapa penulis sebagai palung subduksi, foredeep dalam satu lempeng dan zona sesar mendatar. Kami mengajukan bahwa penjelasan yang memungkinkan adalah model satu lempeng dalam penjelasan keadaan Busur Banda. Model yang dapat diterima untuk Palung Seram adalah foredeep di depan sabuk sesar anjak dan lipatan yang berasosiasi dengan exhumation processes di Pulau Seram dan fitur yang dalam diakibatkan oleh subsidence akibat pembeban jalur sesar anjak dan lipatan. Palung Seram memiliki batimetri yang lebih dangkal, kurang dari 3000m dan merupakan zona aseismik.Kata kunci: Busur Banda, Cekungan Buru, konvergensi, jalur sesar anjak dan lipatan, Palung Seram.